Character competence of the corporation - Sharma, Subhash (2002)
This paper presents the concept of character competence as a basis for creating ethical organizations. In view of the gaps between the `statement' of values and the `state' of values that have been witnessed recently in many corporates, the need to improve character competence of the corporates has become critical to the success of organizations. While corporates pay a lot of attention to core competence, they hardly pay much to character competence. Drawing upon various paradigms of ethics, this paper suggests a holistic framework of business ethics rooted in ethical imperatives for individuals, organizations and markets. The framework developed in the paper forms the foundational basis for the concept of character competence. The author suggests the need for developing a character competence index and rating corporates on such an index. Further, it is suggested that ethical sensitivity can be inculcated through development of ethics-based management models with roots in character competence. - Reproduced.
Keywords: Organizations; Corporate culture